Institutionalizing Justice in Ancient Babylon: Legal Institutions, Royal Authority, and the Code of Hammurabi - Roberth Kurniawan Ruslak Hammar; Imanuel Inriyanto Ruslak Hammar; Odilo D.s Fautngilyanan (Cendekiawan Indonesia Timur, 2026)
This article examines the institutionalization of justice in Ancient Babylon through the legal institutions and forms of authority reflected in the Code of Hammurabi. As one of the earliest written legal collections in human history, the Code provides important evidence of how law was used to organize social relations, regulate economic activity, and legitimize political power. Using normative legal research with historical and conceptual approaches, this study analyzes the legal norms contained in the Code and situates them within the broader social and political structure of Babylonian society. The findings show that Babylonian law was supported by a relatively complex institutional order involving the king, judges, administrative officials, local assemblies, written records, and procedures of proof. Royal authority occupied a central position in this system, deriving legitimacy from divine mandate, especially through the association between Hammurabi and the god Shamash. The institutionalization of justice was reflected in the codification of rules on bodily injury, professional responsibility, economic transactions, family relations, and social hierarchy. Although the legal system was not egalitarian, it provided a formal framework for dispute resolution, social control, and the protection of vulnerable groups. The article argues that the Code of Hammurabi should be understood not merely as a legal text, but as an institutional instrument for consolidating justice, order, and royal legitimacy in Ancient Babylon.